The Impact of Corruption on the Development of the Quality of Human Life in Southeast Asia - Sigit Wahyudi; Rakhmat Alfian (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to conduct an empirical analysis related to the impact of corruption on a country's economy in enhancing the development of the quality of human life in Southeast Asia in the 2012-2018 period. The model used in this study is panel data (pooled data) that combines cross-section data and time series. Corruption in this study is illustrated by the Corruption Perception Index (CPI) value, which means that the higher the level of corruption, the lower the CPI value, and the lower the level of corruption, the higher the CPI value. The results showed that the Corruption Perception Index (CPI) had a positive and significant effect on the development of the quality of human life both directly and through economic conditions. Thus the lower corruption level in a country, the higher the development of the quality of human life. Therefore, it needs more effort to improve the economy and efforts to reduce the number of corruption so that human development in Southeast Asia.